Five Easy Pieces - Rafelson, Bob, 1933-; Billy, Green Bush.; Fannie Flagg; Karen Black; Marlena MacGuire; Richard Stahl; Sally Struthers; Jack Nicholson (USA BBS Productions, 1970)
Robert Dupea has given up his promising career as a concert pianist and is now working in oil fields. He lives together with Rayette, who's a waitress in a diner. When Robert hears from his sister that his father isn't well, he drives up to Washington to see him, taking Rayette with him. There he gets confronted with his rich, cultured family that he had left behind.
A trashy oil rigger returns home to comfort his dying father, where he is confronted with the past he ran away from: A successful career as a classical pianist.
Carole Eastman
Languages: English, German, Italian, Spanish, French Subtitles: English, German, Italian, Spanish, French, Dutch, Arabic, Czech, Danish, Finnish, Greek, Hebrew, Hindi, Hungarian, Icelandic, Norwegian, Polish, Portuguese, Swedish, Turkish
Keywords: Music; Drama